2004
DOI: 10.1210/me.2003-0125
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cardiac-Specific Thyrotoxicosis Increases Myocardial β-Adrenergic Responsiveness

Abstract: Whereas many cardiac symptoms of thyrotoxicosis resemble those of the hyperadrenergic state, circulating catecholamines are reduced or normal in this condition. To test the hypothesis that the thyrotoxic heart is hypersensitive to catechol-amines, we studied beta-adrenergic signaling in a transgenic (TG) mouse in which the human type 2 iodothyronine deiodinase (D2) gene is expressed in myocardium. Because D2 converts T4 to T3, the active form of thyroid hormone, the D2 TG mouse exhibits mild, chronic thyrotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 48 publications
0
27
0
1
Order By: Relevance
“…Biochemical assays Cyclic AMP measurement. The cyclic AMP (cAMP) content of MSTO-211H cells was measured using an [ 125 I]cAMP commercial radioimmunoassay kit (NEK-033; Perkin Elmer, Shelton, CT) according to the manufacturer's instructions and previously described methods (15). Deiodinase activity.…”
Section: Methodsmentioning
confidence: 99%
“…Biochemical assays Cyclic AMP measurement. The cyclic AMP (cAMP) content of MSTO-211H cells was measured using an [ 125 I]cAMP commercial radioimmunoassay kit (NEK-033; Perkin Elmer, Shelton, CT) according to the manufacturer's instructions and previously described methods (15). Deiodinase activity.…”
Section: Methodsmentioning
confidence: 99%
“…It may be responsible, at least in part, for the enhanced catecholamine sensitivity of b1R-coupled cardiac responses in the hyperthyroidism state (Williams et al, 1977;Tse et al, 1980). Decreased levels of Gi in ventricular cells exposed to T 3 may also contribute to the increased b-adrenergic sensitivity (Carvalho-Bianco et al, 2004).…”
Section: General Aspects Of Genomic Signaling Pathwaysmentioning
confidence: 99%
“…The human heart expresses high levels of D2 mRNA in contrast to the low D2 levels in the rodent heart [11,92]. Transgenic mice overexpressing D2 in the myocardium have mild chronic cardiac thyrotoxicosis [132] associated with increased b-adrenergic responsiveness of cardiomyocytes [133,134]. It has been demonstrated that Nkx-2.5 and GATA-4 interact with the TTF-1 binding sites of the human dio2 5'FR and induce D2 expression while the absence of these binding sites results in a lower D2 mRNA level in the rat heart [90].…”
mentioning
confidence: 99%